The Effect of Insider Trading on Insiders' Reaction to Opportunities to 'Waste' Corporate Value - Lucian Arye Bebchuk; Chaim Fershtman (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1990)
This paper analyzes certain effects of insider trading on the principal-agent problem in corporations. Specifically, we focus on those managerial choices that confront managers with the need to decide between options that produce different corporate value but do not differ in the managerial effort involved. In the absence of insider trading, and as long as managers' salaries are positively correlated with their firm's results, managers will make such choices efficiently, and consequently such choices have previously received little attention. We show that, in the presence of insider trading, managers may make such choices inefficiently. With such trading, managers might elect to have a lower corporate value-that is, they may "waste" corporate value-because having such a value might enable them to make greater trading profits. We analyze the conditions under which the problem we identify is likely to arise and the factors that determine its severity. We also identify those restrictions on insider trading that can eliminate this problem.
Keywords: 330